ANALISIS PEMBERIAN REWARD OLEH GURU UNTUK MOTIVASI BELAJAR MATEMATIKA DALAM KURIKULUM MERDEKA - Lina Rihatul Hima; Hersiyati Palayukan (STKIP Andi Matappa, 2022)
The independent curriculum emphasizes the achievement of competence in attitudes, knowledge and skills. The implementation of the independent curriculum is expected to increase students' learning motivation, because this curriculum is basically student-centered. The teacher is only a facilitator and mediator as well as a motivator for students, so that students are enthusiastic in learning and get good results. Mathematics learning is one of the main subjects found at all school levels. In mathematics, there are subject matter that are interrelated with one another. The existence of rewards is expected to provide high motivation and discipline, so that in the teaching and learning process, activities in the classroom can provide high learning motivation, so that students' academic achievement can be improved. This research will be conducted in class X in one of the high schools in the city of Kediri. The activity is carried out in the odd semester of 2022/2023 in August. The research method used is descriptive qualitative. The form of reward given is in the form of verbal and non-verbal rewards, reward rewards and value rewards. The impact of giving rewards given by teachers to students in learning mathematics has an impact on students' learning motivation. Independent curriculum emphasizes the achievement of attitude, knowledge and skill competencies. The implementation of the independent curriculum is expected to increase students' learning motivation, because this curriculum is basically student-centered. The teacher is only a facilitator and mediator as well as a motivator for students, so that students are enthusiastic in learning and get good results. Mathematics learning is one of the main subjects found at all school levels. In mathematics, there are subject matter that are interrelated with one another. The existence of rewards is expected to provide high motivation and discipline, so that in the teaching and learning process, activities in the classroom can provide high learning motivation, so that students' academic achievement can be improved. This research will be conducted in class X in one of the high schools in the city of Kediri. The activity is carried out in the odd semester of 2022/2023 in August. The research method used is descriptive qualitative. The form of reward given is in the form of verbal and non-verbal rewards, reward rewards and value rewards. The impact of giving rewards given by teachers to students in learning mathematics has an impact on students' learning motivation.